Exstrophy of cloaca sequence (OEIS complex) with multiple cardiac malformations (Indian Journal of Case Reports, 2019)
Omphalocele, Exstrophy, Imperforate anus, Spinal defects (OEIS) complex is the most severe birth defect within the exstrophyepispadias complex. There is exstrophy of the cloaca, failure of fusion of the genital tubercles and pubic rami, omphalocele and incomplete development of the lumbosacral vertebrae with hydromyelia. The diagnosis of OEIS complex mainly relies on sonographic findings. Our case presented with microcephaly, omphalocele, syndactyly, hydromyelia, imperforate anus, single cloacal opening, bifid clitoris, prominent unfused pubic rami and left renal agenesis. In addition, multiple severe cardiac malformations were found on echocardiography. Prognosis is poor when the OEIS complex is compounded by life-threatening malformations. We report a rare case of a preterm neonate presenting with features of OEIS complex with multiple cardiac malformations.